The Impact Of Mergers On Company Performances In The Banking Sector - Prakoso, Rezka Bayu; Andreas, Fanri; Firmansyah, Amrie (Politeknik Keuangan Negara STAN, 2023)
This study aims to examine the financial performance of PT Bank Oke Indonesia, which carried out the merger in 2017. This study employs financial performance ratios and stock performance as indicators to overview the effect of mergers on company performance. The research data is sourced from quarterly financial reports from the 1st quarter of 2017 to the 4th quarter of 2021 obtained from the company's website. In addition, research data is also sourced from 3-month stock prices within the same period, derived from www.finance.yahoo.com. Financial performance testing employs descriptive statistical analysis with the Wilcoxon test, while stock performance is tested through stock return value analysis. The test results show that the company's financial performance decreased after the merger. Tests on stock performance also suggest an impairment after the merger. It indicates that the short-term merger carried out by PT Bank Oke Indonesia failed to provide a positive value for the company's financial and stock performance. This study is expected to be additional literature in the accounting field concerning mergers and acquisitions.